UMP focuses on innovation en route to being the main choice of university - UMP, PNC
Denizens of Universiti Malaysia Pahang (UMP) were urged to focus on innovation in all aspects of teaching, learning, research, publication management, administration, leadership and anything that led to brilliancy and made it the global main choice university.